Efektifitas Media Sosial sebagai Alat Promosi pada Sekolah Menengah Kejuruan di Bekasi - Andreas Adi Trinoto (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
When conventional promotion of new student admissions become the only means of marketing at Vocational High School, the new tool and strategy [14] is needed that qualified to face the challenges of technology. With the social media such as Facebook, Twitter and Instagram, its use has become an idea to answer the needs of the school[12]. Primary data collected in the form of quantitative and qualitative, based on a questionnaire survey and interviews on media that has been used. Linear regression was used to seek influence between variables and Diagram Ishikawa / Fishbone, a tool to locate and identify the cause of the problem. This study found that investments in technology, particularly social media has yet not to get the maximum results in the acceptance of vocational students Yadika 6 academic year 2016/2017.